A discrete-time multivariable MRAC scheme applied to a nonlinear aircraft model with structural damage. (March 2015) - Guo, Jiaxing; Tao, Gang
Abstract: In this paper, a new discrete-time multivariable model reference adaptive control (MRAC) scheme is developed and its application to continuous-time nonlinear systems with structural damage is studied, for which several key technical issues are addressed. The relation of the infinite zero structures of the continuous-time nonlinear system and the linearized discrete-time system is established. Invariance properties of the system infinite zero structure and control gain matrix of the linearized discrete-time system under damage are studied for an aircraft flight control application. Desired system stability and asymptotic output tracking are ensured for the linearized discrete-time system with dynamics and damage uncertainties. A discrete-time linearization-based control design is constructed for control of a high-fidelity continuous-time nonlinear aircraft model with uncertain dynamics and structural damage. Simulation results show the desired system performance and demonstrate the effectiveness of the developed discrete-time adaptive control method for the nonlinear aircraft system model. ∇